Sistem Monitoring Kecepatan Motor Induksi Dengan HMI Berbasis PLC - Ikhsan Rifaldo; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
The Induction motors are electric motors that are widely used as propulsion in industry, because of their simpler construction, relatively cheap prices compared to other types of motors, lighter weight and easier maintenance compared to DC motors. To get the induction motor operation as desired, the motor needs to be controlled and supervised or monitored. This paper proposes an induction motor rotation speed monitoring system using a Programable Logic Controller (PLC)-Based Human Machine Interface (HMI). The HMI used is the HMI KTP 700 Comfort with PLC S7 1200 1215C. In addition to monitoring the motor speed, the HMI screen also adds features to operate the motor. This motor speed monitoring system is implemented on a 0.75 kW 3-phase induction motor. The test results in the laboratory show that the induction motor speed monitoring system proposed in this study has worked well, where the induction motor speed data displayed on the HMI screen is close to the same as the motor speed data obtained on the measuring instrument.